2015
DOI: 10.1080/21681376.2015.1088792
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic resilience in Ireland: the roles of industrial structure and foreign inward investment

Abstract: This paper examines the resilience of Irish regions during the course of the post-2007 economic crisis, focusing specifically on employment change in firms in receipt of assistance from the Irish government's enterprise development agencies. The paper classifies both regions and sectors in terms of their employment performance both before and during the recession and employs a number of techniques to assess the roles of sectoral composition, firm nationality and other factors in shaping the recession's regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 11 publications
(16 reference statements)
3
32
0
1
Order By: Relevance
“…A new partitioning model termed multifactor partitioning (MFP) has been developed to correct these errors and to partition growth into two or more variables (Ray, 1990). This analysis therefore joins the growing list of applications of MFP (Barbonne, 2003;Breathnach et al, 2015;Gardiner et al, 2013;Lagravinese, 2015;Lamarche et al, 2003;Ray, 1990Ray, , 1996Ray et al, 2012Ray et al, , 2013. It follows Gardiner et al (2013) and Lagravinese (2015) in tracking the MFP effects cumulatively for each successive period, which in this study is from 1987-1988 to 1987-2012. Using the same base year (1987) ensures comparability of the rates for each period.…”
Section: Methodologies For Partitioning Employment Growthmentioning
confidence: 56%
“…A new partitioning model termed multifactor partitioning (MFP) has been developed to correct these errors and to partition growth into two or more variables (Ray, 1990). This analysis therefore joins the growing list of applications of MFP (Barbonne, 2003;Breathnach et al, 2015;Gardiner et al, 2013;Lagravinese, 2015;Lamarche et al, 2003;Ray, 1990Ray, , 1996Ray et al, 2012Ray et al, , 2013. It follows Gardiner et al (2013) and Lagravinese (2015) in tracking the MFP effects cumulatively for each successive period, which in this study is from 1987-1988 to 1987-2012. Using the same base year (1987) ensures comparability of the rates for each period.…”
Section: Methodologies For Partitioning Employment Growthmentioning
confidence: 56%
“…Ireland is one of the world's most active countries in its industrial policy. Key objectives include promoting export-led growth (Breathnach et al, 2015), generating industry-university R&D partnerships (Barry, 2014b), and developing better linkages between industries (Barry, 2014a;O'Leary and van Egeraat, 2018). One of the key strategies developed to foster linkages and knowledge spillovers between domestic and MNE activities includes the development of collaborative R&D infrastructure and clusters (Department of Jobs, Enterprise and Innovation, 2014), which have been linked to the emergence of industrial clusters (O'Connor et al, 2017).…”
Section: Mnes As Agents Of Structural Changementioning
confidence: 99%
“…In general, Ruane (2016) attributed Ireland's recovery to 'Ireland's large, foreign-owned, modern, export-oriented, multinational sector and its early and sustained action to deal with the fiscal deficit that emerged in 2008'. On the other hand, Breathnach et al (2015) suggested that MNEs were not a key determinant in the recovery, but rather that the industry mix had an important impact. Thus the findings on the role that MNEs play in the regional resilience in Ireland remain contradictory.…”
Section: Regional Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…The substantial difference in exports per plant between foreign and Irish plants in Table 4 while notable is not surprising given the prominence of foreign firms for Irish export performance, along with the impact 'contract manufacturing' can have on official statistics (O'Leary, 2015). The duality of the Irish economy in terms of Irish and foreign-owned economic activity has been widely studied (e.g., Barry & Bradley, 1997;Barry, Görg, & Strobl, 2005;Barry & Hannan, 1995;Breathnach, van Egeraat, & Curran, 2015;O'Leary, 2015). We disaggregate the five largest clusters by exports (2012 value) into Irish and foreign-owned plants in Table 5 to provide further indications of their relative employment, output and wages per worker trends.…”
Section: International Performance Of Clustersmentioning
confidence: 99%